Analisis Faktor - Faktor yang Mempengaruhi Kemiskinan (Studi Kasus di Kabupaten Banjarnegara, Cilacap, Purbalingga, Kebumen, dan Banyumas) - Hendry Wijaya; Istiqomah Istiqomah; Arintoko Arintoko (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of inflation, Gross Regional Domestic Product, and Human Development Index on poverty in Banjarnegara, Cilacap Purbalingga, Kebumen, dan Banyumas Regencies. The data used in this study are secondary data in the period 2000-2019. With the multiple linear regression method panel data. The regression output with the fixed effect model shows that the inflation variable does not have a significant effect on poverty, and the Human Development Index and Gross Regional Domestic Product variables have a negative and significant effect on poverty in Banjarnegara, Cilacap Purbalingga, Kebumen, dan Banyumas Regencies. This finding implies local governments to create jobs and provide training and improve education infrastructure and health infrastructure.